Breath analysis. Physiological basis and sampling techniques. - Wilson, H Kerr (Scandinavian Journal of Work, Environment & Health, 1986)
This paper examines the physiological basis for breath analysis and draws attention to the factors which may affect the blood:breath ratio. A review of recent breath analysis techniques is presented, and some consideration is given to the use of breath analysis in the biological monitoring of workers exposed to solvents.
Keywords: breath analysis; physiology; sampling technique